PROSPECTS FOR ORGANIC FARMING IN ROMANIA - Cristina BURGHELEA; Carmen UZLĂU; Corina Maria ENE; Dan TOPOR (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This article aims to highlight the fact that agriculture is one of the most important economic sectors of the country and it was the field for which implementation of a common policy was provided from the early stages of European construction. One of the key elements of the Common Agricultural Policy, concerning rural development is to promote and develop organic farming.